Bridging student affairs support and student development: A systematic review of how student affairs supports shape comprehensive qualities through student engagement - Zhao, Dong; Nathan, Sanmuga (Edelweiss Applied Science and Technology, 2026)
Student affairs have evolved from administrative functions to strategic mechanisms that promote holistic student development in higher education. However, existing studies remain fragmented, providing a limited understanding of how Student Affairs Supports (SAS) contribute to Student Comprehensive Qualities (SCQ) through Student Engagement (SE). This study conducted a systematic review in accordance with the PRISMA 2020 guidelines. Literature was retrieved from Scopus, Web of Science, CNKI, and Wanfang, and 40 peer-reviewed empirical studies were included after rigorous screening and quality appraisal using the Mixed Methods Appraisal Tool (MMAT). The findings indicate that SAS consists of two complementary dimensions: Digital Intelligence Service Support and Developmental Empowerment Support. Both dimensions enhance students’ behavioral, emotional, and cognitive engagement, thereby fostering Psychological Capital, Career Adaptability, and Civic Literacy. Guided by Astin’s Input–Environment–Outcome (I-E-O) Model and supported by Self-Determination Theory and Multidimensional Student Engagement Theory, this review integrates existing evidence into a coherent conceptual mechanism linking institutional support, student engagement, and comprehensive student development. The review also identifies key research gaps and provides implications for future research and the design of student affairs practices in digitally transformed higher education.